High-Frequency Variation of Purine Biosynthesis Genes Is a Mechanism of Success in Campylobacter jejuni - Andrew Cameron (American Society for Microbiology, 2015)
ABSTRACT Phenotypic variation is prevalent in the zoonotic pathogen Campylobacter jejuni, the leading agent of enterocolitis in the developed world. Heterogeneity enhances the survival and adaptive malleability of bacterial populations because variable phenotypes may allow some cells to be protected against future stress. Exposure to hyperosmotic stress previously revealed prevalent differences in growth between C. jejuni strain 81-176 colonies due to resistant or sensitive phenotypes, and these isolated colonies continued to produce progeny with differential phenotypes. In this study, whole-genome sequencing of isolated colonies identified allelic variants of two purine biosynthesis genes, purF and apt, encoding phosphoribosyltransferases that utilize a shared substrate. Genetic analyses determined that purF was essential for fitness, while apt was critical. Traditional and high-depth amplicon-sequencing analyses confirmed extensive intrapopulation genetic variation of purF and apt that resulted in viable strains bearing alleles with in-frame insertion duplications, deletions, or missense polymorphisms. Different purF and apt alleles were associated with various stress survival capabilities under several niche-relevant conditions and contributed to differential intracellular survival in an epithelial cell infection model. Amplicon sequencing revealed that intracellular survival selected for stress-fit purF and apt alleles, as did exposure to oxygen and hyperosmotic stress. Putative protein recognition direct repeat sequences were identified in purF and apt, and a DNA-protein affinity screen captured a predicted exonuclease that promoted the global spontaneous mutation rate. This work illustrates the adaptive properties of high-frequency genetic variation in two housekeeping genes, which influences C. jejuni survival under stress and promotes its success as a pathogen. IMPORTANCE C. jejuni is an important cause of bacterial diarrheal illness. Bacterial populations have many strategies for stress survival, but phenotypic variation due to genetic diversity has a powerful advantage: no matter how swift the change in environment, a fraction of the population already expresses the survival trait. Nonclonality is thus increasingly viewed as a mechanism of population success. Our previous work identified prominent resistant/sensitive colonial variation in C. jejuni bacteria in response to hyperosmotic stress; in the work presented here, we attribute that to high-frequency genetic variation in two purine biosynthesis genes, purF and apt. We demonstrated selective pressure for nonlethal mutant alleles of both genes, showed that single-cell variants had the capacity to give rise to diverse purF and apt populations, and determined that stress exposure selected for desirable alleles. Thus, a novel C. jejuni adaptive strategy was identified, which was, unusually, reliant on prevalent genetic variation in two housekeeping genes.